Clinical and biochemical footprints of congenital disorders of glycosylation: proposed nosology - Ng, Bobby; Freeze, Hudson H.; Himmelreich, Nastassja; Blau, Nenad; Ferreira, Carlos R. (Molecular genetics and metabolism, 2024)
We have identified 200 congenital disorders of glycosylation (CDG) caused by 189 different gene defects and have proposed a classification system for CDG based on the mode of action. This classification includes 8 categories: 1. Disorders of monosaccharide synthesis and interconversion, 2. Disorders of nucleotide sugar synthesis and transport, 3. Disorders of N-linked protein glycosylation, 4. Disorders of O-linked protein glycosylation, 5. Disorders of lipid glycosylation, 6. Disorders of vesicular trafficking, 7. Disorders of multiple glycosylation pathways and 8. Disorders of glycoprotein/glycan degradation. Additionally, using information from IEMbase, we have described the clinical involvement of 19 organs and systems, as well as essential laboratory investigations for each type of CDG. Neurological, dysmorphic, skeletal, and ocular manifestations were the most prevalent, occurring in 81%, 56%, 53%, and 46% of CDG, respectively. This was followed by digestive, cardiovascular, dermatological, endocrine, and hematological symptoms (17-34%). Immunological, genitourinary, respiratory, psychiatric, and renal symptoms were less frequently reported (8-12%), with hair and dental abnormalities present in only 4-7% of CDG. The information provided in this study, including our proposed classification system for CDG, may be beneficial for healthcare providers caring for individuals with metabolic conditions associated with CDG.
Online verfügbar: 10. April 2024, Artikelversion: 22. April 2024
Gesehen am 22.07.2025